Hybrid Version of the Kedem–Katchalsky–Peusner Equations for Diffusive and Electrical Transport Processes in Membrane - Andrzej Ślęzak; Sławomir M. Grzegorczyn (Membranes)
One of the most important formalisms used to describe membrane transport is Onsager–Peusner thermodynamics (TOP). Within the TOP framework, a procedure has been developed for the transformation of the Kedem–Katchalsky (K–K) equations for the transport of binary electrolytic solutions across a membrane into the Kedem–Katchalsky–Peusner (K–K–P) equations. The membrane system with an Ultra Flo 145 Dialyser membrane used for hemodialysis and aqueous NaCl solutions was used as experimental setup. The H version of K–K–P formalism for binary electrolyte solutions was used to evaluate theoretical coefficients characterizing fluxes of energies and efficiencies for membrane transport processes. The coupling coefficients of membrane processes and the dissipative energy flux were calculated on the basis of the Peusner coefficients obtained from transformation of K–K coefficients. The knowledge of dissipative energy flux, which is a function of thermodynamic forces, allows for the determination of the energy conversions during transport processes in a membrane system. In addition, a frictional interpretation of the obtained coefficients is presented.